The Mediating Role of Corporate Social Responsibility in the Relationship Between Institutional Ownership and Tax Avoidance - Indriyana Puspitosari; Estri Navaranti (Accounting and Finance Studies, 2023)
Tax avoidance is an effort made by the company to reduce tax payments legally. The amount of tax expense paid by the company is very material so that it will affect the amount of profit earned by the company. This study aims to determine the effect of institutional ownership on tax avoidance and the mediating effect of corporate social responsibility. This study analyzes companies in the property & real estate sector listed on the Indonesia Stock Exchange for the period 2016-2021. The sampling technique used was purposive sampling technique, obtained a final sample of 15 companies. Path analysis is used to analyze the indirect relationship between institutional ownership and tax avoidance through corporate social responsibility. The results of the analysis show that institutional ownership has no effect on corporate social responsibility, institutional ownership and corporate social responsibility have no effect on tax avoidance. The results of path analysis did not find the mediating role of corporate social responsibility in the relationship between institutional ownership and tax avoidance.